ANALYSIS OF PLANT NURSERY BUSINESS DEVELOPMENT STRATEGIES AT VIKOM NURSERY BUSINESS IN LANGSA CITY - Hidayat, Muhammad Arfan; Indra, Siti Balqies; Mast, Rini (AGRIBUSINESS JOURNAL, 2024)
This research was carried out with the aim of identifying priority the strategy for developing the plant nursery business at the Vikom Nursery business located on Jl. Medan Banda Aceh, Gampong Teungoh, Kec. Langsa City, Langsa City. The research was conducted in October-November 2023. The method used was SWOT analysis. The results of the IFAS and EFAS matrices obtained alternative SO strategies with a score of 15.801, WO strategies with a score of 14.132, ST strategies with a score of 4.631, and WT strategies with a score of 2.962. The results of the research are based on QSPM analysis so that the main strategic priorities in developing plant breeding businesses at the nursery vikom are obtained, namely that business owners can apply for financial assistance through programs that have been created by the government to help MSMEs in Indonesia so that the results can be additional capital to develop their business. and adding more modern facilities and infrastructure. The suggestion in this research is to implement the main priority alternative strategies that have been produced in this research. After implementing the main priority strategies, business owners can also implement other alternative strategies in this research.